TROPHY-U-01: A Phase II Open-Label Study of Sacituzumab Govitecan in Patients With Metastatic Urothelial Carcinoma Progressing After Platinum-Based Chemotherapy and Checkpoint Inhibitors. Issue 22 (1st August 2021) - Tagawa, Scott T.; Balar, Arjun V.; Petrylak, Daniel P.; Kalebasty, Arash Rezazadeh; Loriot, Yohann; Fléchon, Aude; Jain, Rohit K.; Agarwal, Neeraj; Bupathi, Manojkumar; Barthelemy, Philippe; Beuzeboc, Philippe; Palmbos, Phillip; et al.
Abstract : PURPOSE: Patients with metastatic urothelial carcinoma (mUC) who progress on platinum-based combination chemotherapy (PLT) and checkpoint inhibitors (CPIs) have limited options that offer objective response rates (ORRs) of approximately 10% with a median overall survival (OS) of 7-8 months. Sacituzumab govitecan (SG) is a TROP-2–directed antibody-drug conjugate with an SN-38 payload that has shown preliminary activity in mUC. METHODS: TROPHY-U-01 (ClinicalTrials.gov identifier: NCT03547973 ) is a multicohort, open-label, phase II, registrational study. Cohort 1 includes patients with locally advanced or unresectable or mUC who had progressed after prior PLT and CPI. Patients received SG 10 mg/kg on days 1 and 8 of 21-day cycles. The primary outcome was centrally reviewed ORR; secondary outcomes were progression-free survival, OS, duration of response, and safety. RESULTS: Cohort 1 included 113 patients (78% men; median age, 66 years; 66.4% visceral metastases; median of three [range, 1-8] prior therapies). At a median follow-up of 9.1 months, the ORR was 27% (31 of 113; 95% CI, 19.5 to 36.6); 77% had decrease in measurable disease. Median duration of response was 7.2 months (95% CI, 4.7 to 8.6 months), with median progression-free survival and OS of 5.4 months (95% CI, 3.5 to 7.2 months) and 10.9 months (95% CI, 9.0 to 13.8 months), respectively. Key grade ≥ 3 treatment-related adverse events included neutropenia (35%), leukopenia (18%), anemia (14%), diarrhea (10%), and febrile neutropenia (10%), with 6% discontinuing treatment because of treatment-related adverse events. CONCLUSION: SG is an active drug with a manageable safety profile with most common toxicities of neutropenia and diarrhea. SG has notable efficacy compared with historical controls in pretreated mUC that has progressed on both prior PLT regimens and CPI. The results from this study supported accelerated approval of SG in this population.